2015
DOI: 10.1172/jci77983
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 sustains microglial expansion during aging and response to demyelination

Abstract: Microglia contribute to development, homeostasis, and immunity of the CNS. Like other tissue-resident macrophage populations, microglia express the surface receptor triggering receptor expressed on myeloid cells 2 (TREM2), which binds polyanions, such as dextran sulphate and bacterial LPS, and activates downstream signaling cascades through the adapter DAP12. Individuals homozygous for inactivating mutations in TREM2 exhibit demyelination of subcortical white matter and a lethal early onset dementia known as N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
428
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 401 publications
(477 citation statements)
references
References 59 publications
28
428
2
1
Order By: Relevance
“…Since our results suggested that microglia clear away the myelin fragments that accumulate in the 3 aging brain, we compared microglia number and appearance in young and old animals. Not only had the number of microglia increased in the white matter of old animals as reported previously 11,12 , but also microglia in contact with myelin ( Supplementary Fig. 2).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Since our results suggested that microglia clear away the myelin fragments that accumulate in the 3 aging brain, we compared microglia number and appearance in young and old animals. Not only had the number of microglia increased in the white matter of old animals as reported previously 11,12 , but also microglia in contact with myelin ( Supplementary Fig. 2).…”
supporting
confidence: 81%
“…Not only had the number of microglia increased in the white matter of old animals as reported previously 11,12 , but also microglia in contact with myelin ( Supplementary Fig. 2).…”
supporting
confidence: 81%
“…It has previously been reported that TREM2 is capable of binding microbial and damage-associated molecular signatures found on bacteria (41,42), lipids exposed during axonal injury (23,43), and nucleic acid released from dying cells (29). Here, we report apoE as a novel TREM2 ligand.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 69%
“…Therefore, during experimental conditions that mimic microbial invasion or neural tissue damage, microglial TREM2 is able to bind bacterial fragments (41,42), anionic, zwitterionic, and myelin-associated lipids (23,43), and nucleic acid released from dead cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work demonstrated that loss of Trem2 leads either to microglial degeneration in different diseases of the central nervous system [55,66,11], or conversely to protection [34]. Thus, the exact mechanisms underlying 5-HT 2B R-mediated regulation of microglial survival and the role of scavenger receptors in this response will have to be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%